“De que formação falamos?” Um retrato das Residências Multiprofissionais em saúde mental no Brasil - Rezende, Dalilla Matilde Ferreira de (2023)
The training of healthcare professionals plays a strategic role in the implementation and consolidation of the Unified Health System (Sistema Único de Saúde - SUS), with the development of capabilities being crucial to prepare them to face the challenges arising from social transformations, in alignment with real and dynamic healthcare work contexts, the job market, and professional practice conditions. Among these formative processes, in the field of mental health, multiprofessional residencies have a transformative potential for practices, aligned with Health and Psychiatric Reforms, as well as Permanent Health Education. Therefore, this study aimed to understand the state of the art of Multiprofessional Residency Programs in Mental Health in Brazil. It was an exploratory and descriptive research with a qualitative and quantitative approach, involving field and documentary research. Data sources included admission selection notices for 2022 and Pedagogical Political Projects of active Multiprofessional and/or Integrated Residency Programs in Mental Health in Brazil for 2021 and/or 2022. Data analysis utilized the ATLAS.ti software and thematic analysis. The study presents two relevant technical products for professionals in training and for those responsible for the management and coordination of Mental Health Residency Programs in Brazil. They are: the "Mapping Report of Mental Health Residency Programs in Brazil up to 2022" and the "Consolidated Competency Profile of the Mental Health Professional". To achieve this, the research mapped and characterized 51 active Multiprofessional Residency Programs in Mental Health across the entire Brazilian territory, identifying their geographical distribution, professional composition, and training scenarios. Additionally, this analysis was enriched by investigating 19 Pedagogical Political Projects. From these, key actions were identified and distributed in three competency areas: Health Care, Health Management, and Health Education to consolidate the competency profile of mental health professionals in training in Brazil. The study addresses the complexity of the Mental Health field and the comprehensiveness of care. It discusses the competency profile of professionals delineated at the national level and aligned with public policies related to healthcare residencies and mental health. It emphasizes the interprofessional, interdisciplinary, and intersectoral training of mental health professionals to enhance the quality of mental healthcare, aligned with the psychosocial paradigm and integrated with mental health public policies. This study aims to contribute to the updating and strengthening of active Multiprofessional Residency Programs in Mental Health in Brazil. Additionally, it seeks to provide support for the development of new training initiatives in the field, enhancing the teaching and learning process in mental health for human resources allocated to SUS.